2023
DOI: 10.3389/fpls.2023.1121852
|View full text |Cite
|
Sign up to set email alerts
|

OsGRF4AA compromises heat tolerance of developing pollen grains in rice

Abstract: Extreme high temperature at the meiosis stage causes a severe decrease in spikelet fertility and grain yield in rice. The rice variety grain size on chromosome 2 (GS2) contains sequence variations of OsGRF4 (Oryza sativa growth-regulating factor 4; OsGRF4AA), escaping the microRNA miR396-mediated degradation of this gene at the mRNA level. Accumulation of OsGRF4 enhances nitrogen usage and metabolism, and increases grain size and grain yield. In this study, we found that pollen viability and seed-setting rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The broad spectrum of defects induced by high temperature complicates the molecular analysis of underlying processes and so far, very few molecular factors have been identified that contribute to heat stress tolerance of pollen. In rice, the GROWTH REGULATING FACTOR 4 ( OsGRF4 ), and HEAT SHOCK FACTOR60-3B ( OsHSP60-3B ) are required to secure viability and seed-setting rate under heat stress (Mo et al 2023; Lin et al 2023). And in maize, improved tolerance of meiosis to heat stress has been reported in lines overexpressing HEAT SHOCK PROTEIN101 ( HSP101 ) (Li et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of defects induced by high temperature complicates the molecular analysis of underlying processes and so far, very few molecular factors have been identified that contribute to heat stress tolerance of pollen. In rice, the GROWTH REGULATING FACTOR 4 ( OsGRF4 ), and HEAT SHOCK FACTOR60-3B ( OsHSP60-3B ) are required to secure viability and seed-setting rate under heat stress (Mo et al 2023; Lin et al 2023). And in maize, improved tolerance of meiosis to heat stress has been reported in lines overexpressing HEAT SHOCK PROTEIN101 ( HSP101 ) (Li et al 2022).…”
Section: Discussionmentioning
confidence: 99%